Implementation of Independent Curriculum Material for Phase B Class IV Bhinneka Tunggal Ika: Knowing Indonesian Nation toward Forming Global Diversity Character Students of SDN 210 Babakan Sinyar - Larastuti, Larastuti; Reviyanti, Lysda; Gumilar, Muhammad Ramdan; Rahayu, Ayu Sugiarti (PT. Riset Press International, 2024)
Indonesia's rich and diverse cultural diversity is an important basis for forming student character. The Merdeka curriculum, with the material